PELATIHAN, KEMAMPUAN KERJA DAN PERENCANAAN KARIER BERDAMPAK PADA KINERJA KARYAWAN PDAM KABUPATEN KEDIRI - Anita Sumelvia Dewi (Faculty of Social and Political Science, 2018)
This research is analyze the influence of training, the ability work and development career, of the performance of employees PDAM Kabupaten Kediri. As for research sample areas is 49 employees of PDAM Kediri. An analysis of this research using multiple linear regression using SPSS software, produced the following: all the variables was in also had an impact significantly correlates with the employee performance. For training variables influence the performance of local PDAM company employees tens of thousand of workers Kabupaten Kediri as much as 0.022. For work ability variables, influence the performance employees PDAM Kediri of 0.605 while for development carrer variable influence of 0.266 of the PDAM Kediri employee performances. This research result indicates that to enhance the performance of some of their workers, Kediri district local clean water companies PDAM should prioritize more on the ability of , because been disclosed in the research it produces the regression coefficient the greatest of all ( as much as 0.605 )